TRANSFORMATION OF GONDANG SABANGUNAN TRADITIONAL MUSIC INTO UNING-UNINGAN MODERN MUSIC AT THE BATAK TOBA ETHNIC TRADITIONAL CEREMONY IN DENPASAR CITY - Rianti Simbolon; I Nyoman Suarka; Ni Made Wiasti (E-Journal of Cultural Studies, 2022)
The practice of using music at the Batak Toba ethnic traditional ceremony in Denpasar city has transformed. The transformation was from gondang sabangunan traditional music into uning-uningan modern music. Furthermore, uning-uningan modern music dominated or used more often rather than gondang sabangunan traditional music in Denpasar city. The main factor which causes this transformation is there are no artists who are able to use gondang sabangunan traditional ensemble music. The aims of this study are to know the causes of the transformation of gondang sabangunan traditional music into uning-uningan modern music, the forms of the transformation of gondang sabangunan traditional music into uning-uningan modern music, to figure out the implication of the transformation of gondang sabangunan traditional music into uning-uningan modern music. The results showed that the transformation occurred because of the internal factors which consist of economic factors, artists’ creativity factors, the lack of understanding of the Batak Toba gondang traditional, and the lack of cultural transmission to the young generation. Otherwise, the external factors consist of globalization factors, and pop culture factors. The transformation forms of gondang sabangunan traditional music into uning-uningan modern music such as the formation transformation of music instruments, the transformation in using repertoire types, the position transformation of the musicians, the transformation of execution time, and the musician’s identity transformation. The implications of the transformation of gondang sabangun traditional music into uning-uningan modern music are the fading of gondang traditional music, switching functions into entertainment, the artists are more concerned with material, and the young generation is less familiar with gondang traditional music. Keywords: transformation, gondang sabangunan traditional music, uning-uningan modern